Requirements Engineering for Cyber Physical Production Systems: The e-CORE approach and its application. Issue 104 (February 2022) - Loucopoulos, Pericles; Kavakli, Evangelia; Mascolo, Julien
Abstract: Traditional manufacturing and production systems are in the throes of a digital transformation. By blending the real and virtual production worlds, it is now possible to connect all parts of the production process: devices, products, processes, systems and people, in an informational ecosystem. This paper examines the underpinning issues that characterize the challenges for transforming traditional manufacturing to a Cyber Physical Production System. Such a transformation constitutes a major endeavour for requirements engineers who need to identify, specify and analyse the effects that a multitude of assets need to be transformed towards a network of collaborating devices, information sources, and human actors. The paper reports on the e-CORE approach which is a systematic, analytical and traceable approach to Requirements Engineering founded on a 'capability-oriented' paradigm with particular emphasis on 'early requirements'. The utility of the approach is demonstrated using two use cases from an industrial-size application in the automotive industry and specifically the case of requirements of Fiat Chrysler Automobiles. Highlights: Discusses requirements engineering challenges in the context of CPPS development. Argues for capability as a most suitable metaphor when considering CPPSs requirements. Introduces the e-CORE framework. The utility of e-CORE is demonstrated in a real manufacturing situation. e-CORE enriches traditional RE techniques, seamlessly modelling strategic issues with tactical and operational ones.